Mobilität der Solo-Selbständigen im europäischen Vergleich - Karin Schulze Buschoff; Claudia Schmidt (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– In the past decades self-employment has gained in importance in the majority of EU Member States. In particular the proportion of small and one-person businesses shows an increasing trend. In contrast to the classical research into business start-ups, which usually focuses on sustainability in the sense of the longest possible survival of the enterprises, this paper determinedly goes into the dynamics and flexibility on the labour market of solo-self-employment. In the context of the theory of transitional labour markets, a mobility concept is developed and the dynamics of solo-self-employment in five European countries (Germany, the Netherlands, Italy, Great Britain and Sweden) are compared on the basis of mobility rates and mobility patterns (inflows, outflows, durations). The analyses are based on data from the European Employment Sample (1993-2003) and the European Community Household Panel (1994-2001). The results of the analyses show a higher level of employment mobility of the solo-self-employed compared with other employment forms in all of the countries. Almost every year women show a higher rate of mobility than men in all of the countries. Solo-self-employment also concerns far more people over time than the aggregate data for individual years show at first sight. In the country comparison Germany shows the highest mobility rate of solo-self-employed people (since 1996). Finally the paper looks at the institutional protection of mobility and transitions, which differs from country to country. Taking the state pension insurance systems as an example, the paper shows that with regard to social security law, changes in employment status into and out of solo-self-employment are associated with more or less serious specific disadvantages in all of the countries observed. In Germany, the country with the highest mobility rate of solo-self-employed people, these disadvantages are particularly clear. In the sense of the concept of risk management, the strategy of a European social policy should focus on being able to guarantee a minimum of continuous basic protection despite discontinuous employment histories. Depending on the way that the social security systems are organised nationally, there is in this respect a more or less urgent need for action.
Keywords: 330; Kleinstunternehmen; berufliche Selbständigkeit; Unternehmensgründung; berufliche Mobilität; Berufsverlauf; Bundesrepublik Deutschland; Niederlande; Italien; Schweden; Großbritannien